Actual issues of the implementation of social security of military personnel of the Armed Forces of Ukraine in modern conditions - Diachenko , Serhii; Tsiukalo , Liudmyla (Social Development and Security, 2019)
The article deals with the modern legal framework that regulates the issues related to social security of the military of the Armed Forces of Ukraine. One of the components of the personnel social security - pension - is analyzed. Peculiarities of pension provision of personnel retired from military service are considered. The focus is on the issues of recalculation of pensions due to changes in legislation. Ways to improve the pension provision of persons retired from military service considered are proposed.